Characterization of lipidic plaque materials at calcified atheroma: its association with calcification thickness evaluated by optical coherence tomography and near-infrared spectroscopy imaging. (3rd October 2022) - Mitsui, K; Kataoka, Y; Murai, K; Kitahara, S; Iwai, T; Sawada, K; Matama, H; Honda, S; Fujino, M; Takagi, K; Yoneda, S; Otsuka, F; et al.
Abstract: Introduction: The degree of calcification and its thickness have been considered to affect stent expansion, leading to an increases risk of repeat revascularization in patients receiving PCI. Pathophysiologically, accumulation of lipidic materials within vessel wall could trigger the formation of plaque calcification. Elucidating characteristics of lipidic plaque components at calcified atheroma may enable to identify phenotypes with thick calcification which less likely responds to PCI. Purpose: This study investigated the relationship of calcification thickness with lipidic plaque materials at calcified atheroma by using OCT and near-infrared spectroscopy (NIRS) imaging. Methods: We analyzed 52 calcified lesions (culprit/non culprit lesions=44/8) in 47 CAD patients (stable CAD/ACS=36/11) from the REASSURE-NIRS registry (NCT04864171). OCT and NIRS imaging evaluated 4-mm segment exhibiting maximum superficial calcification arc. Calcification thickness on OCT imaging, its arc on IVUS imaging, and NIRS-derived lipid arc were analyzed at every 1-mm interval cross-sectional images. In addition, yellow-calcification ratio (YCR = lipid arc/calcification arc) was calculated (Figure 1). Results: 53% of study subjects exhibited chronic kidney disease and 70% of them received a statin (averaged on-treatment LDL-C =89mg/dL). Throughout OCT and NIRS/IVUS imaging analysis of 260 cross-sectional images, the averaged calcification arc, its maximum thickness, lipid arc and YCR were 210° (167–285°), 0.78mm (0.62–0.95mm), 95° (31–169°) and 0.33 (0.09–0.59), respectively. As expected, thicker calcification more likely exhibited a greater calcification arc (r=0.30, p<0.001). Furthermore, a greater thickness of calcification was associated with smaller lipidic plaque burden, reflected by yellow arc (r=−0.36, p<0.001) and YCR (r=−0.36, p<0.001) (Figure 2). After adjusting age, gender and ACS, calcification arc (p<0.001) and YCR (p<0.001) continued to predict thicker calcification. Conclusion: Thickening of calcification was associated with severer calcification arc, which was accompanied by the shrinkage of lipidic plaques. Our findings suggest the evaluation of lipidic plaque component as a potential tool to identify calcified atheroma harbouring thick calcification, which may cause a greater risk of stent underexpansion. Funding Acknowledgement: Type of funding sources: None.